Key to the success of the outlet shopping centers located in optimal site - Sikos T., Tamás (Hungarian Geographical Bulletin, 2009)
Outlet centers embody a unique type of shopping centers; their emergence can be traced back to the existence of factory outlets. In the beginning they were established to offer the company’s products to employees and factory workers at a reasonable price as a kind of fringe benefit. Obviously, producers offered products which could not be sold through traditional distribution channels. Another distinguishing feature of outlet centers is that a remarkable part of the goods comes from commercial channels so in many cases some of them have no articles in all sizes. This study provides a comparative analysis between an Austrian and a Hungarian outlet center to demonstrate their good market position and to explain the main reasons of their success.